Human-Lemur Coexistence in a Multiple-Use Landscape - Chen-Kraus, Chloe; Raharinoro, Njaratiana A.; Randrianirinarisoa, Miravo A.; Anderson, David J.; Lawler, Richard R.; Watts, David P.; Richard, Alison F. (Frontiers in Ecology and Evolution, 2022)
Human impacts on the natural world are increasing and are generally considered a threat to wildlife conservation and the persistence of species. However, not all human activities are antithetical to conservation and not all taxa are impacted in the same ways. Understanding how wildlife respond to human activities at the population and individual level will help inform management of landscapes where humans and wildlife can coexist. We examined the effects of anthropogenic activities on a critically endangered primate, Verreaux’s sifakas (Propithecus verreauxi), at a multiple-use reserve in southwest Madagascar. Specifically, we sought to determine which activities the sifakas perceived as disturbances, using the framework of the risk disturbance hypothesis (RDH). The RDH holds that animals will respond to perceived disturbances as they do to predation threats. We therefore predicted that sifakas would be more vigilant, spend more time in high forest strata, reduce their daily feeding time, and occur at lower densities in response to high levels of perceived disturbance. Using data on sifaka behavior and spatial distribution, and the frequencies of anthropogenic activities, we found that sifakas increased vigilance and their height above the ground in response to certain human-related activities, notably those of domestic dogs. Contrary to our predictions, however, we did not find a negative effect of anthropogenic activities on daily activity budgets or population density. The relationship between the occurrence of sifakas and the intensity of tree cutting was actually positive. Our results indicate that sifakas perceive certain anthropogenic activities as threats and respond with immediate behavioral shifts, but that these activities do not have a discernible negative impact on the reserve’s population at this time. These results suggest that lemur conservation can be successful even in areas that are subject to moderate human use.